A new way to classify and retrieve reusable components: the finder metaphor - Barros Justo, José Luís (1999)
Our research group ISRI (InCormation Syslems Reuse on Internet) is working in a new classification scheme for reusable software (assets) based on the idea of hyper-spherical finders. The Finder metaphor deals with a multidimensional space where the components are positioned according to its functional description. and vision fields. hiper-spheres, which can move in space and see the components. Our approach has some advantages over other techniques and methodologies, for example: we start with an empty space (the universe) and automatically fill it with reusable assets, which describe the application domain, but the space itself is dynamically generated as components are inserted; furthermore, we can build different finders, alter its radius or its kind of movement, without the need of reclassifying the repository, allowing a dynamical classification. We developed and tested a simple but practical method to compute similarities, allowing to locate assets in this kind of universe, generating finders and modifying them, querying the universe and retrieving similar components. The tested values of recall and precision were similar or better than other known methods but ours is by far easier to implement and maintain. An extensive list of references about reuse and classificationlretrieval problem. where interested readers can investigate more deeply is offered.